Phase 3 Study Evaluating Brexanolone, a GABAA Receptor Modulator, in Severe Postpartum Depression [29B]. (May 2018) - Meltzer-Brody, Samantha; Kanes, Stephen; Riesenberg, Robert; Rubinow, David; Maximos, Bassem; Colquhoun, Helen
Abstract : INTRODUCTION: A double-blind, placebo-controlled Phase 2 study of brexanolone (USAN; formerly SAGE-547 Injection), a positive allosteric modulator of GABAA receptors, demonstrated rapid and durable improvements in postpartum depression (PPD). The current study (NCT02942004) is one of two randomized, double-blind, placebo-controlled Phase 3 studies that evaluated the efficacy and safety of brexanolone in women with PPD. METHODS: Approximately 120 women with severe PPD (Hamilton Rating Scale for Depression [HAM-D] total score ≥26) were randomized 1:1:1 to 60-hour infusions of blinded placebo or brexanolone at 60 or 90 µg/kg/h. The primary endpoint was the change from baseline in the mean HAM-D total score at Hour 60 following brexanolone compared with placebo. Durability of effect and safety were assessed through Day 30. Safety and tolerability were assessed by adverse events, vital signs, laboratory evaluations, electrocardiogram, and the Columbia Suicide Severity Rating Scale. Secondary efficacy endpoints included change from baseline in the Montgomery-Åsberg Depression Rating Scale, HAM-D response, HAM-D remission, and Clinical Global Impression-Improvement. RESULTS: This Phase 3 study will be completed in 2017. This presentation will be the first comprehensive reporting of primary and secondary endpoints. These data seek to validate and expand upon the Phase 2 results, which showed a rapid reduction in mean HAM-D score (Hour 60, brexanolone -21.0 vs. placebo -8.8, p=0.008) and durability through Day 30 (20.8 vs. -8.8, p=0.010). CONCLUSION: This study, along with a companion Phase 3 study with brexanolone in subjects with moderate PPD, seeks to validate and expand upon the earlier Phase 2 data.